2015
DOI: 10.1002/ange.201503595
|View full text |Cite
|
Sign up to set email alerts
|

Nachwachsende Rohstoffe: das Problem der Katalysatordesaktivierung und Wege zu seiner Lösung

Abstract: Das vergangene Jahrzehnt war Zeuge vielzähliger Forschungsarbeiten zur Umwandlung biobasierter Rohstoffe in Kraftstoffe und Chemikalien. Während der Forschungsschwerpunkt auf der Entwicklung neuer aktiver und selektiver Katalysatoren liegt, findet deren langfristige Stabilität weit weniger Aufmerksamkeit. Dieser Aufsatz erörtert die Hauptanforderungen an langfristige Katalysatorstabilität, diskutiert einige Grundlagen und schlägt Wege zum Erreichen dieses Ziels vor. Drei wesentliche Probleme werden besprochen:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…• Humin formation and solutions for prevention; 170 • Improving MOF characterization methods regarding their catalytic properties.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…• Humin formation and solutions for prevention; 170 • Improving MOF characterization methods regarding their catalytic properties.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The catalysts were prepared by dispersing group 8–11 hydrogenation metals and, optionally, various promoters over high‐surface area supports. The catalyst constituents were selected to resist hydrothermal conditions [25] . Accordingly, the metals were limited to Cu, Co, Pd, Pt and Ru, while the supports included active carbons, ZrO 2 , TiO 2 as well as amorphous silica‐alumina (ASA).…”
Section: Resultsmentioning
confidence: 99%
“…[2] GVL can be obtained by the catalytic hydrogenation of levulinic acid (LA), which is obtainedb yh ydrolytic conversion of lignocellulosic biomass; most of the studies were performed with the use of ap ressurized externalsource of hydrogen. [5] Later,w er eported that the phase compositiono f the TiO 2 support directly influenced the catalytic performance of the Ru catalysts;t he highest activity was observed for an anatase/rutile mixed phase support when compared with the counterpart catalysts on pure anatase or rutile phase supports. [4] The nature of the catalyst support has also been reported to be of high importance, and TiO 2 has provent ob eap romising candidate for supporting Ru nanoparticles for the production of GVL.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Lange indicated that TiO 2 was as upport of high interesto wing to its good mechanicala nd thermal stabilityu nder hydrothermala nd acidic conditions. [5] Later,w er eported that the phase compositiono f the TiO 2 support directly influenced the catalytic performance of the Ru catalysts;t he highest activity was observed for an anatase/rutile mixed phase support when compared with the counterpart catalysts on pure anatase or rutile phase supports. [6] This behavior was relatedt ot he selectivedeposition of Ru with optimum size distribution on the rutile fractiono ft he mixed-phase support.I nc ontrast, the formation of either Ru crystallites that weret oo small or too strongly interactingw ith the large surface areao fp ure rutile, or Ru aggregates that were too large on the pure anatase phase, resultedi nc atalysts with low activity.…”
Section: Introductionmentioning
confidence: 99%